The phylogeography and ecology of Oligobrachia frenulate species suggest a generalist chemosynthesis-based fauna in the arctic. Issue 3 (March 2023) - Sen, Arunima; Andersen, Liselotte W.; Kjeldsen, Kasper U.; Michel, Loïc N.; Hong, Wei Li; Choquet, Marvin; Rasmussen, Tine L.
Abstract: We used ancient DNA (aDNA) extraction methods to sequence museum voucher samples of Oligobrachia webbi, a frenulate siboglinid polychaete described from a northern Norwegian fjord over fifty years ago. Our sequencing results indicate a genetic match with the cryptic seep species, Oligobrachia haakonmosbiensis (99% pairwise identity for 574 bp mtCOI fragments) . Due to its similarity with O. webbi, the identity of O. haakonmosbiensis has been a matter of debate since its description, which we have now resolved. Furthermore, our results demonstrate that chemosynthesis-based siboglinids, that constitute the bulk of the biomass at Arctic seeps are not seep specialists. Our data on sediment geochemistry and carbon and nitrogen content reveal reduced conditions in fjords/sounds, similar to those at seep systems. Accumulation and decomposition of both terrestrial and marine organic matter results in the buildup of methane and sulfide that apparently can sustain chemosymbiotic fauna. The occurrence of fjords and by extension, highly reducing habitats, could have led to Arctic chemosymbiotic species being relatively generalist with their habitat, as opposed to being seep or vent specialists. Our stable isotope analyses indicate the incorporation of photosynthetically derived carbon in some individuals, which aligns with experiments conducted on frenulates before the discovery of chemosynthesis that demonstrated their ability to take up organic molecules from the surrounding sediment. Since reduced gases in non-seep environments are ultimately sourced from photosynthetic processes, we suggest that the extreme seasonality of the Arctic has resulted in Arctic chemosymbiotic animals seasonally changing their degree of reliance on chemosynthetic partners. Overall, the role of chemosynthesis in Arctic benthos and marine ecosystems and links to photosynthesis may be complex, and more extensive than currently known.